Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Barómetro Municipal 2017. Relatório de dados quantitativos. - IESE (Instituto de Estudos Sociais e Económicos (IESE), 2018)
É o novo relatório de pesquisa produzido por uma equipa de investigadores do Instituto de Estudos Sociais e Económico (IESE), coordenada por Salvador Forquilha, no quadro de um projecto de investigação em curso sobre a avaliação dos munícipes em relação ao desempenho da governação municipal em Moçambique. Este primeiro “Barómetro da Governação Municipal 2017” (BGM) explora dados quantitativos relativos à percepção dos munícipes sobre as diferentes vertentes da actuação dos órgãos e serviços municipais e que podem permitir às autoridades municipais melhor conceberem os seus planos de governação e a responderem de maneira mais eficaz às expectativas dos munícipes. Refira-se que nesta primeira fase do projecto BGM foram abrangidos oito municípios, cobrindo diferentes regiões do país, nomeadamente Beira, Ilha de Moçambique, Lichinga, Manjacaze, Nampula, Pemba, Quelimane e Tete.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; governance / governação

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Parte IV - Eleições, Governação Local e Sociedade Civil - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº2 Uma nota sobre o recenseamento eleitoral IDeIAS Nº5 Beira – o im da Renamo? IDeIAS Nº6 Sem surpresas: abstenção continua maior força política na reserva em Moçambique … até quando? IDeIAS Nº8 Sobre os votos nulos IDeIAS Nº20 Sobre a transparência eleitoral IDeIAS Nº22 Uma análise preliminar das eleições de 2009 IDeIAS Nº48 Sobre resultados eleitorais e dinâmica eleitoral em Sofala IDeIAS Nº50 Uma relexão sobre o calendário e o recenseamento eleitoral para as eleições autárquicas de 2013 IDeIAS Nº38 Comissão Nacional de Eleições: uma reforma necessária IDeIAS Nº83 Rever o sistema eleitoral IDeIAS Nº3 Orçamento participativo: um instrumento da democracia participativa IDeIAS Nº16 A primeira reforma iscal autárquica em Moçambique IDeIAS Nº18 Relexões sobre parcerias público-privadas no inanciamento de governos locais IDeIAS Nº21 Pequenos provedores de serviços e remoção de resíduos sólidos em Maputo IDeIAS Nº41 Estado e informalidade: como evitar a “tragédia dos comuns” em Maputo? IDeIAS Nº66 Reformas de descentralização e serviços públicos agrários em Moçambique: porquê persistem os desaios? IDeIAS Nº70 Autonomização local para quê? Questões económicas no debate sobre autonomia local IDeIAS Nº24 Sociedade civil em Moçambique e no mundo IDeIAS Nº27 Sociedade civil e monitoria do orçamento público IDeIAS Nº58 As “revoltas do pão” de 2008 e 2010 na imprensa IDeIAS Nº61 Indignai-vos! IDeIAS Nº19 “O inimigo é o modelo”! Breve leitura do discurso político da Renamo IDeIAS Nº62 Media e campanhas eleitorais
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; governance / governação

As Autoridades Tradicionais nos Processos de Governação Descentralizada em Moçambique - Campos, Luciana Martins (Universidade Federal de Pernambuco, 2017)
A partir da década de 1990 iniciou-se, em vários países da África Subsaariana, um movimento de liberalização e descentralização política com a adoção de regimes democráticos. Associado a esse processo se têm em curso reformas administrativas e legislativas que visam incorporar as autoridades comunitárias e tradicionais à administração pública local a partir do reconhecimento de sua importância social e representativa para certas comunidades rurais, onde a presença do Estado se faz menor ou de modo deficitário. No entanto, esse lugar de importância social e cultural das autoridades tradicionais, em específico, só existe enquanto herança do Estado bifurcado colonial, conduzindo à elaboração de um sistema misto de governo na atualidade, onde as autoridades tradicionais seguem desempenhando funções “administrativas” semelhantes às exercidas no período colonial na lógica do indirect rule. As relações das autoridades tradicionais com o Estado em termos de administração local expõe uma situação de hibridismo institucional em decorrência do desafio de penetração do Estado enquanto administração pública e burocrática que, portanto, coabita com lógicas informais de funcionamento da administração e da realidade jurídica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; authority / autoridade; decentralization / descentralização; governance / governação

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Accountability Through Active Citizenship: Improving Petroleum Governance in Ghana, Mozambique & Tanzania - Arregui, Chiqui (Oxfam America, 2015)
The objective of the baseline survey is to analyze and document the situation around accountability, transparency and governance of the O&G sector in the country prior to the implementation of the Oxfam project. It focuses on a selected group of indicators chosen for the country program logical framework, identified and approved in the Baseline Inception Phase. A total of 33 people were interviewed in the context of this baseline. This was accompanied by a thorough national and international literature review. It was not possible to gain access to some key Government and CSO representatives at sub-national level and any of the three O&G companies contemplated in the context of this baseline, which could affect the comprehensiveness of findings. It is expected that a similar exercise be conducted at the end of the program to gauge the changes brought about by program interventions. The fieldwork for the baseline was conducted in December 2014. Baseline findings are presented in line with program outcomes, broadly focusing on building the capacities of (i) communities (Outcome 1); (ii) CSOs and the media (Outcome 2) and (iii) Other stakeholders (Outcome 3).
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; governance / governação

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental

Displacement and Dispossession Through Land Grabbing in Mozambique: The Limits of International and National Legal Instruments - Twomey, Hannah (Refugee Studies Centre (RSC), 2014)
This working paper examines the limitations of international and national law to address displacement and dispossession from land grabs within the case study of Mozambique. The main question that I seek to answer is: What limits international and national law in addressing displacement and dispossession due to land grabs in Mozambique? I will argue that the limits of law to address displacement and dispossession are not due to a lack of institutionalising international good governance norms into domestic-level legal frameworks. Nor can the limits be attributed to state incapacity. Rather, the limits of law lie within the norm implementation process, wherein norms are conditioned by the local Mozambican governance context to serve domestic interests
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; governance / governação; land governance / gestão de terra

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

Orientacoes superiores: Time and bureaucratic authority in Mozambique - Gonçalves, Euclides (African Affairs, 2013)
This article examines the production, circulation, and interpretation of regulatory documents in contemporary Mozambique in order to highlight their central importance to processes of governance. The empirical focus is on orientações superiores – written and oral documents issued by ﬁgures and institutions of authority with the intention of advising on procedures for policy formulation and implementation. By producing orientações superiores in a way that leaves their intent ambiguous and their status provisional, party and state ofﬁcials shift the focus of policy making from substance to process. In this way, bureaucratic authority is produced and reinforced through the manipulation of the timing of policy implementation. This perspective expands current understandings of African governance that on the whole have been limited to the analysis of the effectiveness of African institutions and policies, leaving the tactical effects of ambiguity, timing, and provisionality in policy implementation undertheorized.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - ethnography / etnografia; authority / autoridade

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

The politics of poverty: Elites, citizens, and states - findings from ten years of DFID-funded research on governance and fragile states 2001-1010 - UK DFID Research and Evidence Staff (UK Department for International Development (DFID), 2010)
This research adds depth to our understanding of development as a political process, provides rich evidence based on country experience, and points to the questions which aid agencies must address in order to be effective – including in more fragile countries. It demonstrates that durable reforms need to be constructed, nationally and locally, in a way that fits each political context and it challenges donors to build the capacity to contribute to this effectively
Keywords: *indexed; *tagged; L - english / inglês; citizenship & participation / cidadania e participação; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; decentralization / descentralização; fragility / fragilidade; governance / governação; poverty / pobreza; taxation / tributação